Lost and found in translation the Kuzari translations of Judah Ben Qardaniel and other Medieval translators - Bar-Asher, Avishai (2023)
This article is dedicated to the lost translation of the Kuzari by Judah ben Isaac ben Qardaniel and discusses previous attempts by scholars to identify remnants of this work. The author aims to identify newly discovered quotations and remnants of the Kuzari using recently discovered manuscript evidence. According to the accumulated evidence, in addition to the well-known translation by Judah ben Saul ibn Tibbon and Samuel ben Judah ben Meshullam of Marseille’s revision of Ibn Tibbon’s work, there are two or three partial or complete medieval translations of the Kuzari. The author sorts and categorizes the different pieces and characterizes each of the translations.
Keywords: Kuzari; Judah ben Isaac ben Qardaniel; Judah ben Saul ibn Tibbon; Samuel ben Judah of Marseilles; Medieval Hebrew Translations